Pengaruh Informasi Akuntansi dan Permintaan Investor terhadap Underpricing - Pradnyadevi, Made Aida; Suardikha, I Made Sadha (E-Jurnal Akuntansi; Vol 30 No 3 (2020), 2020)
Underpricing is a phenomenon that often occurs from IPO activities on the IDX. Underpricing is the difference in stock prices that occur in the primary .market’ and secondary’ market, where the bid price is lower than the closing price of the first trading day. The purpose of this research is to find out the effect of accounting information and investor demand on underpricing.This research was conducted’.at companies whose IPO on .the’ Stock .Exchange in 2016-2018. Data collection was obtained from the collection of prospectuses and company financial statements. The total sample of 81 companies using a purposive sampling method. The analysis technique used is multiple linear regression analysis. This study proves that profitability and firm size negatively affect underpricing, while financial leverage and investor demand have no effect on underpricing . Keywords: Underpricing; Profitability; Company Size; Investor Demand.